The Influence of Learning Styles on The Learning Outcomes of Students in Grade 5 at SDN Ciporos 3 - Febri Isnawati; Amalia Nurul Azizah (International Journal of Science and Applied Science: Conference Series, 2021)
This study aims to determine the effect of learning styles on the learning outcomes of grade 5 students at SDN Ciporos 3. The research method used is quantitative using survey techniques and questionnaires as data collection tools. The sample for this study was 60 grade 5 students who were randomly selected from the student population at SDN Ciporos 3. The results showed that there was a significant influence between learning styles and learning outcomes of grade 5 students at SDN Ciporos 3. Visual and kinesthetic learning styles had a positive effect on learning outcomes, while auditory learning styles did not have a significant effect.